Analysis of e-commerce providers’ role in solving the issues of retail e-commerce logistics in jakarta (study case of pt. Accommerce solusi lestari) - Haryanto, Jony Oktavian; Chang, Florencia Irene (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2018)
The rapid growth of retail e-commerce in Indonesia is not supported by good logistics infrastructure resulting in various logistics issues. This research focuses on analyzing the role of e-commerce provider in solving retail e-commerceÃ¢â‚¬â„¢s logistic issues in Jakarta through a qualitative research. Interview, field work, and supporting theories are used as the source of data. Researcher uses triangulation method to ensure the validity and reliability of the research. The researcher found out that one of the most important requirements for solving retail e-commerce logistics issues in Jakarta is technology utilization.Ã‚Â